2021
DOI: 10.1038/s41467-021-23390-8
|View full text |Cite
|
Sign up to set email alerts
|

Modifying redox properties and local bonding of Co3O4 by CeO2 enhances oxygen evolution catalysis in acid

Abstract: Developing efficient and stable earth-abundant electrocatalysts for acidic oxygen evolution reaction is the bottleneck for water splitting using proton exchange membrane electrolyzers. Here, we show that nanocrystalline CeO2 in a Co3O4/CeO2 nanocomposite can modify the redox properties of Co3O4 and enhances its intrinsic oxygen evolution reaction activity, and combine electrochemical and structural characterizations including kinetic isotope effect, pH- and temperature-dependence, in situ Raman and ex situ X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
247
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(292 citation statements)
references
References 74 publications
13
247
0
Order By: Relevance
“…Besides intrinsic chemical properties, interface engineering has been taken to enhance stability. [ 226,227 ] The distinctive carbon‐coated Co 3 O 4 nanoarrays are highly active and acid‐durable for oxygen evolution with a small overpotential (370 mV) to reach 10 mA cm −2 and exhibit a lifetime long for 86.8 h at a constant current density of 100 mA cm −2 ( Figure 13 a,b). [ 67 ] It is demonstrated that in situ‐formed amorphous carbon by pyrolysis of glucose provides a mechanical supporting layer to hinder exfoliation of catalysts, engendering significantly improved stability even though mass transfer might be slightly influenced by the layered coating.…”
Section: Representative Catalystsmentioning
confidence: 99%
“…Besides intrinsic chemical properties, interface engineering has been taken to enhance stability. [ 226,227 ] The distinctive carbon‐coated Co 3 O 4 nanoarrays are highly active and acid‐durable for oxygen evolution with a small overpotential (370 mV) to reach 10 mA cm −2 and exhibit a lifetime long for 86.8 h at a constant current density of 100 mA cm −2 ( Figure 13 a,b). [ 67 ] It is demonstrated that in situ‐formed amorphous carbon by pyrolysis of glucose provides a mechanical supporting layer to hinder exfoliation of catalysts, engendering significantly improved stability even though mass transfer might be slightly influenced by the layered coating.…”
Section: Representative Catalystsmentioning
confidence: 99%
“…[99] Co 3 O 4 nanowire arrays with Ag doped on FTO substrate also sustained OER activity by 1.91 V with onset potential of current density 10 mA/cm 2 and exhibited high stability at overpotential of 370 mV for 10 h. [100] Studies have found that the introduction of CeO 2 nanocrystals can also improve the intrinsic catalytic activity of Co 3 O 4 . [101] Through the in situ Raman and ex situ XAS structure characterization of the Co 3 O 4 /CeO 2 catalyst before and after the OER test (Figure 5E,F), it was found that the introduction of CeO 2 changed the electronic structure of Co 3 O 4 and created a more favorable local bonding envi-ronment for Co 3 O 4 . Co 3 O 4 surface species are easily oxidized to OER active Co IV species, and the charge accumulation of Co 3 O 4 is inhibited under electrochemical conditions, which is the key to reducing the pre-redox of Co 3 O 4 in the acidic OER, and effectively promotes the massive remodeling of the catalyst surface, thereby improving the acidic OER activity.…”
Section: Noble Metal Free Nanocatalystsmentioning
confidence: 96%
“…(F) In situ Raman spectra of Co 3 O 4 (left panel) and Co 3 O 4 /CeO 2 (right panel) at various constant potentials (vs. RHE) without iR correction (increased from 1.22 to 1.87 V and then back to 1.22 V). Reproduced with permission: Copyright 2021, Nature Publishing Group [101] Tafel slope, without dependence on proton concentration. [97] γ-MnO 2 showed OER performance at a current density of 10 mA/cm 2 with overpotential of 428 mV in acidic media, and by doping with TiO 2 its stability was further improved (Figure 5B,C).…”
Section: Noble Metal Free Nanocatalystsmentioning
confidence: 99%
“…[181] These enhancement mechanisms can also be applied to several systems, such as NNTM sulfide, [183] phosphide, [184] high entropy oxide, [185] and metal-organic framework. [186] Apart from the aforementioned function, rare-earth metals also display some other attractive functions: [71,[187][188][189][190][191][192][193][194][195] i) alloying with other NNTMs to form the newly structured intermetallics with high conductivity, ii) binding with anions to serve as a confinement substrate to anchor the single metal atom, and iii) taking rare-earth element oxides or hydroxides as the coupling subunit to build heterointerfaces. On the basis of the Brewer-Engel theory, [187] alloying the NNTMs that have empty or half-filled vacant d orbitals with rare-earth metals with empty and vacant d orbitals is a viable strategy to design the advanced electrocatalysts for HER.…”
Section: Insights Into the Improvement Of Activity By Rare-earth Metalsmentioning
confidence: 99%